Early Continuous Renal Replacement Therapy In Patients With St-Elevation Myocardial Infarction And Covid-19 After Percutaneous Coronary Intervention: A Case Report - Lubis, Bastian; Amelia, Putri; Akil, Muhammad; Viandy, Vincent; Winata, Ade; WH George, Yohanes (CoinReads Media Prima, 2022)
Background: Currently, there is no standardized approach to managing critically ill COVID-19 patients with acute kidney injury and ST-elevation myocardial infarction. Continuous renal replacement therapy is a routinely used technique in managing critical patients in the intensive care unit. This procedure is applicable in patients with unstable hemodynamic, renal, or non-renal indications, such as removing the excess urea and creatinine from patients with acute kidney injury or clearing the tumor necrosis factor from patients with systemic inflammations. Method: This was a retrospective case report, after analysis of patient clinical data. The patient provided written informed consent to publish their case details and any accompanying images. The study protocol complies with the requirements of the institute’s committee of Haji Adam Malik Hospital, Medan, Indonesia. Results: This report presents a case of ST-Elevation myocardial infarction with COVID-19 infection and acute kidney injury who successfully managed by percutaneous coronary intervention and continuous renal replacement therapy. This patient was prepared for percutaneous coronary intervention and intubated with consideration of strict infection control. To improve the outcomes, we performed continuous renal replacement therapy with continuous venovenous hemodiafiltration mode. The patient improved with a stable hemodynamic and better renal function after 24 hours of continuous renal replacement therapy. Conclusion: Early continuous renal replacement therapy might be beneficial in treating COVID-19 patients with AKI, who previously underwent percutaneous coronary intervention for ST-elevation myocardial infarction.